On the Crossroads of Knowledge or Th e Age of Topicality: Problems of Greek and Roman Art as Part of General Classical Studies - Jijina, Nadia C. (Actual Problems of Theory and History of Art, 2013)
Introduction to the set of articles that discuss the art of Classical antiquity presents the variety of problems considered by the authors of the published materials. Form in art and form thinking, creating, reproducing and replicating settled statuary types and schemes once worked out in Classical antiquity, as well as their usage by the artists of the Early modern history and later, reconstructing compositions that are now lost, and their interpretation, copying of art pieces, studying pastiche — these are the questions put up by the authors, and based on the fundamentals of art criticism.